Revitalization of Local Religious Traditions in Islamic Education: A Literature Study on the Role of Local Wisdom as Green Da'wah - Al-Jauhariyah, Ni’matullah; Albab, Ahmad Ulil; Huda, Miftachul (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The growing complexity of the global environmental crisis demands an Islamic da'wah approach that is not only spiritual but also ecological. The concept of Green Da'wah, or environmentally conscious da'wah, has emerged as a strategic approach to cultivating Muslim awareness of their role as khalīfah fī al-arḍ (vicegerents on Earth). Within Indonesian society, a range of local religious traditions, such as nyadran, sedekah bumi, tahlilan, and slametan, contain ecological wisdom that holds significant potential as instruments for both Islamic da'wah and education. This study aims to theoretically examine the integration of local wisdom found in these religious traditions with Islamic ecological principles, and to explore the role of Islamic education as a medium for revitalizing such traditions in response to modernity and environmental degradation. Employing a qualitative approach through library research, this study analyzes scholarly references from Islamic sources, cultural anthropology, Islamic education, and ecotheology. The findings reveal a convergence of values between local traditions and Islamic teachings on living harmoniously with nature, which can be implemented through culturally rooted Islamic education. Institutions such as Islamic boarding schools and madrasas hold strategic potential in shaping students' ecological character through contextualized curricula grounded in local wisdom. These findings underscore the importance of integrating local traditions into Islamic education as a sustainable and culturally embedded strategy for ecological da'wah.